Understanding factors influencing safety and team functionality at operative vaginal birth through multidisciplinary perspectives: a mixed methods study - Sasha M. Skinner; Eleanor Kippen; Daniel L. Rolnik; Peter Neil; Ryan J. Hodges; Nadine Murry; Ben W. Mol; Arunaz Kumar (BMC Pregnancy and Childbirth)
Abstract Background Operative vaginal birth (OVB) relies on effective teamwork to optimise outcomes. This study aims to explore providers’ perspectives of factors influencing safety and team functionality at OVB. Methods This mixed methods study involved four maternity sites at Monash Health, Australia. Surveys sent to healthcare providers invited quantitative and qualitative appraisal of safety and team functionality at OVB. Semi-structured interviews further explored themes emerging from survey responses. Categorical survey data were compared between staff roles using Pearson’s chi-squared tests. Thematic analysis of free-text survey responses and interviews identified themes influencing safety and team functionality at OVB. Findings We received 100 survey responses from obstetric (n = 41), midwifery (n = 52) and paediatric (n = 7) staff, including senior (n = 49) and junior (n = 51) roles. Overall, 99% thought team communication should improve and 82% had witnessed practices outside protocol. Obstetric versus midwifery or paediatric staff were less likely to rate communication as low or very low quality (5% vs. 29%, p = 0.010). Reporting being extremely or very confident to escalate concerns was more likely in obstetric versus midwifery or paediatric staff (49% vs.12%, p = 0.003) and senior versus junior staff (44% vs. 10%, p = 0.008). Five overarching themes impacted on team functionality at OVB; (1) Quality of communication, (2) Preparation and risk assessment, (3) Leadership and interpersonal dynamics, (4) Transfer from Birth Unit to Operating Theatre, (5) Variation in clinical practice. Discussion Some care providers perspectives of team functionality at OVB differed, with midwifery and paediatric staff more likely to report challenges with communication and were less empowered to escalate concerns. Training in factors impacting team functionality at OVB should be considered.